Cultivating stakeholders’ willingness to participate in sustainable tourism development: A research proposition - Hashemi, Shiva; Singh, Karpal Singh Dara; Xiang, Erjuan (International Journal of Asian Social Science, 2024)
This study aims to evaluate the role of community stakeholders in fostering sustainability within tourism development, with a focus on Langkawi, Malaysia. It seeks to propose a comprehensive model that highlights the influence of residents' perceptions (as key stakeholders) of community empowerment, political trust, and place attachment on their support for sustainable tourism. This study proposes a conceptual framework based on stakeholder theory and conducts a thorough examination of stakeholders' perspectives on tourism development, considering both positive and negative impacts. A comprehensive literature review is adopted in this research. The study reveals nuanced insights into stakeholders' attitudes towards tourism development and sustainability. It identifies the intricate interplay between perceptions of community empowerment, political trust, place attachment, and support for sustainable tourism initiatives, contributing to a deeper understanding of the dynamics surrounding sustainable tourism. Findings indicate that positive perceptions of benefits encourage active resident engagement in STD. Practical implications suggest that local authorities, destination managers, and policymakers should prioritize involving residents in tourism planning, building trust, and empowering communities. By addressing both social and environmental concerns, sustainable tourism can ensure long-term success and balance development with conservation. The proposed model lays the groundwork for future empirical analyses to yield meaningful insights for governments and tourism planners, facilitating informed policy-making and decision-making processes regarding residents and tourism development in developing nations.